Safety and pharmacodynamic dose response of short-term prednisone in healthy adult subjects: a dose ranging, randomized, placebo-controlled, crossover study. Issue 1 (December 2016) - Fleishaker, Dona; Mukherjee, Arnab; Whaley, Fredrick; Daniel, Shanthini; Zeiher, Bernhardt
Abstract Background Glucocorticoids (GCs), such as prednisone, are the standard of care for several inflammatory and immunologically mediated diseases, but their chronic systemic administration is severely limited by serious adverse effects that are both dose and time dependent. Short-term treatment (7–14 days) with oral prednisone is used for many acute inflammatory and allergic conditions. This study was conducted to characterize the safety and pharmacodynamic (PD) dose–response of a 7-day course of oral prednisone on biomarkers of GC receptor agonism. Methods In this randomized, single-blind, placebo-controlled, crossover study (A9001309), 37 healthy subjects received placebo or a prednisone dose from 2.5–60 mg daily over 7 days in each of three treatment periods. White blood cell counts and plasma samples for measuring cortisol, osteocalcin and procollagen type 1 N-propeptide (P1NP) were obtained at 2, 4, 8, and 12 h post-dose on Day 1, immediately prior to dosing on Days 1, 2, and 4, and at nominal dosing time on Days 0 and 8. Urine samples for urinary N-terminal cross-linked telopeptide of type 1 collagen (uNTX) were collected on Days 0, 1, 2, 4, and 8. Serum samples for adiponectin were obtained prior to dosing on days 0, 1, 4 and 8. Results Daily doses of prednisone up to 60 mg resulted in dose- and time-dependent decreases in plasma osteocalcin, plasma P1NP, serum cortisol, and absolute blood eosinophil counts. Absolute blood neutrophil counts increased, while blood lymphocyte counts rebounded to an increased level following an initial rapid decrease after dosing. An increase was observed for uNTX and adiponectin. The incidence of adverse effects with prednisone was not dose related, and nervous system disorders, mainly headache, were the most frequently reported adverse effects. Conclusions This characterization provides important and relevant information on safety and PD responses of short-term prednisone dosing over the commonly-used clinical dose range, and also provides a reference for early clinical development of dissociated agents targeting a differentiated PD profile. Trial registration number NCT02767089 (retrospectively registered: 21 April 2016).